Սփյուռքահայությունը և Հայկական հարցի լուծման խնդիրը (1945 – 1947 թթ.) - Քրիստինե Մելքոնյան (ՀՀ ԳԱԱ հրատ.)
После победы СССР над фашистской Германией среди армян, проживающих в Америке, Европе, на Ближнем и Среднем Востоке, возросла вера в решение Армянского вопроса и возвращениe их на родину – в Советскую Армению. В диаспоре начали создаваться армянские национальные советы, которые внесли неоценимый вклад в решение Армянского вопроса. В 1945–1947 гг. обсуждение Армянского вопроса на международной арене не дало положительных результатов. При этом в поствоенные годы армянской диаспорой была разработана новая стратегия, которая в дальнейшем положила начало процессу признания и осуждения Армянского геноцида парламентами многих стран. After the victory of the USSR over fascist Germany among the Armenians living in America, Europe, Near and Middle East, the belief of the solution of the Armenian Question and their returning home – to Soviet Armenia increased. In the Diaspora the Armenian national councils which brought invaluable contribution to the solution of the Armenian Question started to be created. In 1945–1947 the discussion of the Armenian Question in international scene didn’t give positive results. In spite of this in post-war years the Armenian Diaspora had developed a new strategy which later on began the process of recognition and condemnation of the Armenian Genocide by parliaments of many countries.
Keywords: History; Political Science; D History; J Political Science